A STUDY ON AUTHORSHIP PATTERN IN ESTUARY RESEARCH [2015-2018] - V, Arulmozhi.; K., Sanjeevi. (International Journal of Psychosocial Rehabilitation, 2025)
Estuarine ecosystem is the most productive and protective ecosystem in the marine environment. It has been carried out many of the important functions like feeding, breeding for few marine organisms. It has a buffer zone of the marine ecosystem and protects organisms from the natural calamities. The present study attempts to analyze the authorship pattern of the published documents on estuary research for the period from 2015 to 2018. The primary data for the present study was collected from Web of Science database and totally 11805 records were retrieved for analysis. The analysis includes the year-wise publications, estuary contributions by Top 10 authors, Authorship pattern, Average Author per Publication and Degree of collaborations in the chosen field. The results show that year-wise publications maximum number of articles 3159 was published in 2018. The author Zhang J has contributed 110 articles and the three author contribution is dominant (2965 publications). The range of Average Author per Publication is 3.57 in 2018. The mean value of the Degree of Collaboration is 0.89.